THE RELATIONSHIP OF FINANCIAL STRATEGIES AND DYNAMICS OF DEVELOPMENT OF INDUSTRIAL COMPANIES - A. V. Stepanyan (Стратегические решения и риск-менеджмент)
Apattern of mutual independence of financial position of industrial companies and credit institutions was identified. The issues of development of industrial companies in difficult economic conditions, the causes and consequences of deterioration of credit institutions, the issues of control over the flow of funds from the real sector of the economy to the financial sector are studied as cause-effect relationships in development of industrial companies and the overall change in the macroeconomic environment.